Mortaja blanca, enfermedad de la papa causada por el hongoRosellinia sp. (1990)
Principal biological aspects of the soil-borne fungus Rosellinia sp. causal agent of the potato "Mortaja Blanca" is presented. The obtained results in Latinoamerica by different researches and by the autor respect to disease symptoms on potato crop; pathogenis etiology; its in vitro management; favorable factors for the fungus developing and the integrated control of the disease are described.